(untitled) (Journal of Shaheed Suhrawardy Medical College, 2023)
Objectives: The purpose of this study is to evaluate the endoscopic approach for sinonasal inverted papilloma and outcome of the surgical management. Study design: Retrospective. Place and duration of study: Dhaka Medical college Hospital and Bangladesh ENT Hospital Ltd. of Bangladesh, from January 2006 to December2020. Materials and methods: 189 cases of Inverted papillomas (confirmed by histopathology) presented in last 15 years were managed by Endoscopic Sinus Surgery and the outcome evaluated. Results: The age of the patients ranged from 41 to 80 years. The mean age was 60 years with Male Female ratio 2.04:1.165 patients had unilateral disease and 24 patients had bilateral. Hundred & seventy two patients with inverted papilloma resected by the endoscopic approach,09 patients by nasoendoscopy in combination with modified Caldwell-Luc approach and 8 patients by combined external and nasoendoscopic approach. Follow up revealed recurrence in nine patients. Conclusion: Findings suggest that endoscopic approach is a safe and effective way of treating sinonsal inverted papilloma. Most lesions were entirely resected through endoscopic approach. Importantly surgical strategies need to be thoughtfully chosen based on tumor stage to achieve maximum removal of the lesion and prevent recurrence. J Shaheed Suhrawardy Med Coll 2021; 13(2): 126-129